The detection of ascorbic acid in orange (Rutaceae Sp.) using titration technique - Erlyn Sufitri; Emelda Emelda; Muhammad Abdurrahman Munir; Veriani Aprilia (DAS Institute, 2023)
Vitamin C is a vitamin that belongs to the group of water-soluble vitamins. Some sources of vitamin C are obtained from fresh vegetables and fruits. Vitamin C has several functions in the body, including helping to replenish the body's supply of twins and optimizing functionality. This study aims to determine the levels of vitamin C in lime, kaffir lime, tangerine, and lemon by the iodometric titration method. The sample used in this study was obtained from the Brosot market, Kec. Galur, Kab. Kulon Progo, Yogyakarta. The vitamin C levels obtained from lime, kaffir lime, tangerine, and lemon were 0.004%, 0.004%, 0.002%, and 0.005%.